(untitled) (Web of Teachers: Inderscience Research, 2024)
The article examines the features of creativity development in future teachers using problem-based educational technologies. Psychological-pedagogical conditions of formation of students’ creative potential are described. The expediency of using heuristic methods in the process of professional training of future teachers is based and their use in the organization of training is analyzed.